Modes of Governance and Revenue Flows in African Mining
XV, 253 p.
Keywords: Academics, policy-makers and practitioners from Africa and beyond document new ways of thinking about issues concerning governance and revenue flows in mining activities in Ghana, Mali and the Democratic Republic of the Congo.